The involvement of HDAC3 in the pathogenesis of lung injury and pulmonary fibrosis - Yu, Hanming; Liu, Shi; Wang, Shuo; Gu, Xiu (Frontiers in Immunology, 2024)
Acute lung injury (ALI) and its severe counterpart, acute respiratory distress syndrome (ARDS), are critical respiratory conditions with high mortality rates due primarily to acute and intense pulmonary inflammation. Despite significant research advances, effective pharmacological treatments for ALI and ARDS remain unavailable, highlighting an urgent need for therapeutic innovation. Notably, idiopathic pulmonary fibrosis (IPF) is a chronic, progressive disease characterized by the irreversible progression of fibrosis, which is initiated by repeated damage to the alveolar epithelium and leads to excessive extracellular matrix deposition. This condition is further complicated by dysregulated tissue repair and fibroblast dysfunction, exacerbating tissue remodeling processes and promoting progression to terminal pulmonary fibrosis. Similar to that noted for ALI and ARDS, treatment options for IPF are currently limited, with no specific drug therapy providing a cure. Histone deacetylase 3 (HDAC3), a notable member of the HDAC family with four splice variants ( HD3α, -β, -γ, and-δ), plays multiple roles. HDAC3 regulates gene transcription through histone acetylation and adjusts nonhistone proteins posttranslationally, affecting certain mitochondrial and cytoplasmic proteins. Given its unique structure, HDAC3 impacts various physiological processes, such as inflammation, apoptosis, mitochondrial homeostasis, and macrophage polarization. This article explores the intricate role of HDAC3 in ALI/ARDS and IPF and evaluates its therapeutic potential the treatment of these severe pulmonary conditions.